2021
DOI: 10.1016/j.ijnss.2021.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of lifestyle behavior, anxiety and depression in Chinese college freshman: A cross-sectional survey

Abstract: Objectives First-year college students had exposure to unhealthy lifestyle behaviors that correlate with a high prevalence of anxiety and depression. Regarding to the modifiable lifestyle behaviors factors, this study investigated the prevalence and correlation of multiple lifestyle behaviors, anxiety and depression in a sample of Chinese first-year college students. Methods Cross-sectional data were extracted from Residents eHealth app of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 70 publications
2
11
0
Order By: Relevance
“…With respect to sleep, our finding was consistent with a previous study ( 22 ) which found that insufficient sleep was associated with a higher risk of suicide-related behaviors (e.g., consider suicide, and attempt suicide) among adolescents. One recent cross-sectional study showed a higher risk of suicide-related behaviors in those with insufficient sleep than those without sleep problems ( 21 ).…”
Section: Discussionsupporting
confidence: 92%
“…With respect to sleep, our finding was consistent with a previous study ( 22 ) which found that insufficient sleep was associated with a higher risk of suicide-related behaviors (e.g., consider suicide, and attempt suicide) among adolescents. One recent cross-sectional study showed a higher risk of suicide-related behaviors in those with insufficient sleep than those without sleep problems ( 21 ).…”
Section: Discussionsupporting
confidence: 92%
“…With respect to sleep, our finding was consistent with a previous study (22) which found that insufficient sleep was associated with a higher risk of suicide-related behaviors (e.g., consider suicide, and attempt suicide) among adolescents. One recent cross-sectional study showed a higher risk of suiciderelated behaviors in those with insufficient sleep than those without sleep problems (21).…”
Section: Discussionsupporting
confidence: 92%
“…Their study found that religion (Buddhism and Christianity) was significantly associated with anxiety. As for other religions, the result was statistically insignificant ( p = 0.372) [ 40 ]. In the present study it was shown using logit models that if a person professed Christianity, the chance of increased STAI total score, and therefore anxiety level, decreased by over 40%.…”
Section: Discussionmentioning
confidence: 99%